Design of a feasible high-efficiency 63NiO/ZnO integrated betavoltaic battery. (22nd February 2023) - Yuan, Xinxu; Lu, Jingbin; Zheng, Renzhou; Zhang, Xue; Chen, Ziyi; Li, Xiaoyi; Li, Chengqian; Liu, Yumin; Liang, Lei; Song, Zhigang
Abstract: The conventional betavoltaic battery design fails to eliminate the inherent influence of the radioactive source self-absorption effect, leading to a bottleneck in the efficiency and power of betavoltaic batteries. In this paper, a feasible high-efficiency 63 NiO/ZnO integrated betavoltaic battery is designed and compared with the conventional betavoltaic battery. Simulation results show that the proposed betavoltaic battery has better output performance and breaks the upper limit of efficiency and power. The work presented here provides valuable insights for radioisotope battery designs, and the physical modeling procedure discussed can serve as a good reference for further applications in simulating heterojunctions of type-II semiconductors.